Agrupamento de notas: aplicação do conceito interpretativo na obra estudo para trompete em Dó, de Camargo Guarnieri - Moura Junior, Nivaldo Camargo de (2017)
Abstract: The present research was developed through the application of the Group of Notes, concept presented by James Morgan Thurmond (1991) in the book: Note Grouping: A Method for Achieving Expression and Style in Musical Performance, being used as tool for interpretative suggestion in the work Estudo Para Trompete em Dó, by the Brazilian composer Camargo Guarnieri. Initially a bibliographical survey was carried out on the research and repertoire productions related to the interpretive practices for solo trumpet in Brazil, as well as a historical and methodological linkage of musical expressiveness, approaching the pedagogy of musical expressiveness, the grouping of notes and finally the application of this concept as an interpretative suggestion in specific sections of the work, object of study researched.